2009
DOI: 10.1007/s00264-009-0815-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of late periprosthetic femur fractures: a retrospective cohort of 72 patients

Abstract: We present our series of 72 patients with periprosthetic fractures. The Vancouver classification was used to evaluate the fractures; there was one type A, seven type B1, 42 type B2, 17 type B3 and five type C fractures. Demographics, pre and postoperative data using Charnley-D'Aubigne-Postel score for assessment of function were recorded. The mean follow-up for all patients was two years. The overall outcome of treatment was graded as excellent, good or poor. An excellent result indicated that the arthroplasty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…One major factor that cannot be simulated in such a biomechanical study is the loosening of the stem components. From various investigations, we know that this is a major stress riser for a periprosthetic fracture [10,11]. Some studies have shown that, even for interprosthetic fractures, the loosening between the cement and the stem plays an important role and occurs in most described cases [3].…”
Section: Discussionmentioning
confidence: 99%
“…One major factor that cannot be simulated in such a biomechanical study is the loosening of the stem components. From various investigations, we know that this is a major stress riser for a periprosthetic fracture [10,11]. Some studies have shown that, even for interprosthetic fractures, the loosening between the cement and the stem plays an important role and occurs in most described cases [3].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of periprosthetic femoral fractures presents a major clinical challenge in orthopaedic surgery [13]. Because of both the increase in average life span and the current popularity of hip-replacement, including revision procedures, this type of fracture is likely to be encountered more often in the future.…”
mentioning
confidence: 99%
“…Previous studies on femoral stem revision for periprosthetic have reported dislocation rates between 3.6% and 20.8%. 12,[16][17][18] This is particularly problematic in patients who have had several previous operations, rendering the abductor mechanism incompetent.…”
Section: Discussionmentioning
confidence: 97%
“…This will generally occur within the first 6 postoperative months. 12,17,18,24,27 Subsidence may be minimized by restricting weight-bearing in the early postoperative period while osseointegration of the uncemented stem takes place. However, it was still evident in those series which adopted limited weight-bearing in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation